Creation of mathematical models for ordering graph edges of the pipeline distribution network - Самойленко, Николай Иванович; Гавриленко, Ирина Александровна; Сенчук, Татьяна Сергеевна (Eastern-European Journal of Enterprise Technologies, 2015)
The paper describes the analytical calculation method of functional reliability in pipeline systems. The proposed method allows to determine the relative time period during which a particular user of the distribution pipeline system is able to obtain the desired product, depending on the structure of the pipeline network and reliability of its individual elements. The method is focused on the pipeline networks that, by their structural complexity, are commensurate with the complexity of pipeline transportation systems that operate in different sectors of the economy. The method includes seven successive stages. The paper considers the second stage regarding the transformation of the initial data, presented in the normal production form, into the form that provides the best conditions for the numerical simulation of the whole calculation. The set-theoretical models for ordering graph edges, allowing, on the one hand, to preserve their arbitrary numbering, on the other - to provide algorithmic ease of software for the automated calculation were developed. The corresponding software for free use, implementing the process of ordering the sequence of graph edges in accordance with the proposed mathematical models in unlicensed programming language DevC++ was created.